Leveraging lean in ancillary hospital services : creating a cost effective, standardized, high quality, patient-focused operation - Protzman, Charles; Kerpchar, Joyce; Mayzell, George (Productivity Press, 2015)
This book is part of a series of titles that are a spin-off of the Shingo Prize-winning book Leveraging Lean in Healthcare: Transforming Your Enterprise into a High Quality Patient Care Delivery System. Each book in the series focuses on a specific aspect of healthcare that has demonstrated significant process and quality improvements after a Lean implementation. There are many departments within a hospital that support the primary function of caregiving and each can benefit from implementing Lean methodologies. Leveraging Lean in Ancillary Hospital Services: Creating a Cost Effective, Standard.